Recombinant Antibody-Based and Computer-Aided Comprehensive Analysis of Antibody’s Equivalent Recognition Mechanism of Alternariol and Alternariol Monomethyl Ether - Wang, Zile; Chen, Ling; Zheng, Pimiao; Wang, Jianyi; Ren, Zhenhui; Zhang, Huixia; Zhang, Liang; Jiang, Haiyang (Frontiers in Chemistry, 2022)
Alternariol (AOH) and alternariol monomethyl ether (AME) are two main Alternaria mycotoxins that endanger human health. In this study, a single-chain antibody fragment (scFv) capable of equivalently and specifically recognizing AOH and AME was firstly expressed, and its equivalent recognition mechanism was discussed. The active binding cavity of the antibody was formed by complementarity determining regions (CDRs) of the heavy chain and CDR3 of the light chain. C9 site, which was always exposed outside the binding cavity, made the structural differences between AOH and AME could be ignored. Due to the high similarity of structures, AOH and AME interacted with almost the same amino acids on scFv. The main interaction force was hydrogen bond, and the two toxins had similar bond lengths. So that, C9 was considered to be the key site that determines the equivalent recognition of AOH and AME in the process of hapten modification. These results laid a theoretical foundation for further research on antibodies against Alternaria mycotoxins. It could promote the rapid detection of AOH and AME in food and provided a new idea for targeted preparation of antibodies that could recognize multiple hazards with similar structures.